2015
DOI: 10.1016/j.brs.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Vagus Nerve Dermatome in the External Ear is Protective in Rat Cerebral Ischemia

Abstract: Background Although cervical vagus nerve stimulation is effective for reducing infarct volume in rats, it is not feasible for acute human stroke as it requires surgical incision of the neck. We hypothesized that stimulation of the dermatome in the external ear innervated by the vagus nerve (auricular vagus nerve stimulation; aVNS) reduces infarct volume after transient focal ischemia in rats. Methods Animals were randomized to active aVNS or sham stimulation. For aVNS, electrical stimulation of the left cavu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…We have previously shown that electrical stimulation of the dermatome corresponding to the auricular branch of the vagus nerve in the external ear using needle electrodes reduces ischemic injury after transient MCAO in healthy adult rats and could be a practical alternative to the invasive cVNS. [22] The present study extends our prior report by showing an infarct reducing effect of another novel transcutaneous stimulation method. We have used a non-invasive stimulator that requires placement of a pair of surface electrodes to the skin overlying the vagus nerve in the neck.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have previously shown that electrical stimulation of the dermatome corresponding to the auricular branch of the vagus nerve in the external ear using needle electrodes reduces ischemic injury after transient MCAO in healthy adult rats and could be a practical alternative to the invasive cVNS. [22] The present study extends our prior report by showing an infarct reducing effect of another novel transcutaneous stimulation method. We have used a non-invasive stimulator that requires placement of a pair of surface electrodes to the skin overlying the vagus nerve in the neck.…”
Section: Discussionsupporting
confidence: 88%
“…Number of positive cells in these regions per microscopic field were counted from three consecutive sections and averaged for each animal blindly to the treatment groups. [22]…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned, anatomical tracing studies in the cat (Nomura et al, 1984) and rat (He et al, 2013a) have shown that the ABVN projects to the NTS. Evidence that NTS neurones are activated following ABVN stimulation is derived from studies in which electrical stimulation of the concha in rats with transient focal ischemia elicits c-fos staining in the bilateral NTS and locus coeruleus (Ay et al, 2015a).…”
Section: Mechanism Of Action Of Tvns On Cardiac Functionmentioning
confidence: 99%
“…Previous work in animal models has shown that VNS activates nucleus tractus solitarius (NTS), locus ceruleus (LC) and dorsal raphe nuclei (DRN) [4; 21; 22; 32], all of which can suppress CSD susceptibility by enhancing serotonergic or β-adrenergic activity [29; 42; 46; 56]. VNS has been effective for the treatment of seizures and depression which show a strong clinical association with migraine [27], and many migraine prophylactic drugs are antiepileptics or antidepressants, and suppress CSD [5].…”
Section: Introductionmentioning
confidence: 99%